Analisis Perbandingan Kinerja Keuangan Sebelum Pandemi dan Semasa Pandemi Covid-19 pada Perusahaan yang Terdaftar di Bursa Efek Indonesia (Studi Kasus PT Hero Supermarket Tbk Periode 2018-2022) - Nurwinda Anjani; Rola Manjaleni (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research is motivated by the impact of the Covid-19 pandemic felt by PT Hero Supermarket Tbk on the sustainability of its financial performance. PT Hero Supermarket Tbk recorded a decrease in net income of 26.99% in 2020. The contribution of income from the food and non-food segments both decreased by double digits. So that in 2020 PT Hero Supermarket Tbk will bear losses for the year of up to 1.21 trillion. The aim of this research is to determine the financial performance of PT Hero Supermarket Tbk before the pandemic and during the Covid-19 pandemic. And to find out the comparison of the financial performance of PT Hero Supermarket Tbk before the pandemic and during the Covid-19 pandemic. This research is quantitative research. The data collection technique in this research is a documentation technique in the form of PT Hero Supermarket Tbk's annual financial report for the 2018-2022 period. Before the pandemic, PT Hero Supermarket Tbk's liquidity and profitability ratios were in the good category. However, during the Covid-19 pandemic it got much worse in the poor category. The liquidity and profitability ratios of PT Hero Supermarket Tbk before the pandemic and during the pandemic were significantly different. The ratio results before the pandemic were good, but the results decreased significantly during the Covid-19 pandemic in the second and third years.